Cognitive Load Factor in Failure to Solve the Simple Problem of Prospective Mathematics Teachers - Yohanes, Barep (J-PiMat : Jurnal Pendidikan Matematika, 2025)
The lack of problem-solving skills among prospective mathematics teachers has an impact on the future development of school mathematics instruction. Problem solving is one of the process standards that must be implemented in mathematics education. Therefore, the problem-solving abilities of prospective mathematics teachers must be enhanced to support the advancement and improvement of mathematics learning. This study analyzes the cognitive load factors contributing to the failure of prospective mathematics teachers in solving simple problems, particularly in determining the length of the sides of a right triangle when the hypotenuse is known. Based on Cognitive Load Theory (CLT), errors in problem solving can be influenced by intrinsic cognitive load (material complexity), extraneous cognitive load (instructional design), and germane cognitive load (the effort invested in learning). This study employed a qualitative method, using error analysis from tests and interviews. The results show that students experienced failures in understanding the problem, planning strategies, executing strategies, and evaluating outcomes. The study concludes that the complexity of the intrinsic cognitive load was not balanced by an increase in germane cognitive load through effort investment in problem-solving activities. Germane cognitive load serves as a supporting factor in developing problem-solving skills to overcome the challenges of element interactivity associated with intrinsic cognitive load.Keyword: Cognitive Load, Failure, Problem Solving, Prospective Mathematics Teachers